Strategic technology leveraging making outsourcing work for you - Jonash, Ronald S.
Ronald S. Jonash foresees a new role for the CTO as the technological alter ego of his or her CEO.
As companies master the processes of outsourcing and collaboration, the role of the CTO will change dramatically-ideally, becoming a CEO's technological alter ego.
As companies are challenging their R&D groups to do more with less, and faster; these companies are becoming more and more dependent on outsourcing and collaboration for their competitiveness. But few R&D managers are willing to be accountable for relationships, processes and results they cannot control, and there are significant new challenges when technology collaboration involves different cultures and organizational goals. "Strategic technology leveraging" is a new approach that requires : A fundamental reevaluation of technology strategy in the context of multiple-technology sources and partnerships; a new set of processes to manage "seamless" innovation, and product development involving suppliers, customers and other partners; and a new set of resource management guidelines and budgeting processes. Most importantly, "strategic technology leveraging" requires a significant expansion in the role and responsibility of the chief technology officer-to incorporate explicit accountability for creating and capturing the maximum value of technology leveraged through both internal R&D and the full range of passive and active suppliers, joint ventures and alliances, acquisitions and licensing, universities, consortia, etc.
Keywords: Strategic technology; Outsourcing